Proposed Classification of Midline Lingual Canal: A CBCT Study - Mansi A. Khatri; Yesha V. Jani; Reeta Jha; Deepankar Misra; Siddharth G. Modi; Harmi Patel (Journal of Pharmacy and Bioallied Sciences)
Background: Cone-beam computed tomography (CBCT) has identified some important anatomical landmarks in inter-foraminal region, which can contribute to the explanation of hemorrhagic and nervous disturbances occurring in this region following implant placement. Materials And Methods: The study included 100 subjects. CBCT scans were performed. The number of midline lingual foramina and their diameter was measured. The length of the midline lingual canal, direction, and distances of the canal from the crest of the ridge, lower border of mandible, labial cortex, and lingual cortex were measured. Results: All subjects showed at least one Midline Lingual Canal (MLC). The average diameter was 1.67 mm. Average length of the canal was 7.34 mm. Thirty percent of subjects are in group N (single canals), 70% of subjects are in group M (multiple canals). The maximum canals were in D2 group (80%). Conclusion: CBCT can facilitate the visibility of MLC, if any. Clinicians should take note of the position of the midline mandibular lingual canal and approach this area with caution.